Noninvasive Prenatal Test Raises Concern Over Screening Strategies and the Role of Ultrasound - Tercanli, S.; Vial, Y.; Merz, E. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Several weeks ago a flyer announcing a “summer sale” for noninvasive prenatal testing (NIPT) at significantly reduced rates was distributed throughout Switzerland. The use of this term in connection with a novel prenatal diagnostic method for Down’s syndrome and other trisomies that continues to pose new challenges in this sensitive field is highly unusual and vexing.Aggressive marketing in prenatal medicine is new and unusual in this part of the world and has been rejected in particular by US professional organizations 1. While price reductions may be good news, a responsible approach following basic ethical rules in this sensitive context is more than desirable. There are still fundamental concerns including test performance as well as ethical aspects which need to be broadly discussed and resolved by consensus.For decades, ultrasound screening has been offered as part of prenatal care in particular to detect multiples, growth disturbances, maternal risks such as preeclampsia, anomalies of placentation as well as placental location, and fetal malformations. The rate of severe congenital anomalies is around 3 – 4 % with about 1 % being chromosomal disorders. Prenatal chromosome testing of amniotic fluid cells retrieved by amniocentesis from 16 weeks of gestation onwards was introduced in the 1970s. In the 1980s chorionic villus sampling (CVS) performed from 11 weeks of gestation onwards became established as an earlier screening method. Randomized trials revealed a procedure-related pregnancy loss rate of 0.5 – 1 % for both approaches. For many years advanced maternal age was the main indication for fetal karyotyping. Since more than 30 % of all mothers are now 35 years or older in most industrialized countries, improved screening parameters have been established.The measurement of the fetal nuchal translucency (NT) between 11 + 0 and 13 + 6 weeks of gestation provides the best discrimination between pregnancies with trisomy 21 or other aneuploidies and non-affected fetuses. Large prospective multicenter trials confirmed a detection rate of approximately 90 % with an FPR of 5 % for trisomy 21. This “combined test” includes NT, maternal serum markers, such as free ß-hCG and pregnancy-associated plasma protein A (PAPP-A), and maternal age 23.Additional sonographic findings such as the absence of the nasal bone, tricuspid valve insufficiency, and an abnormal blood flow in the ductus venosus increase the sensitivity or lower the false-positive rate 24.The exclusive consideration of maternal age prior to invasive testing no longer meets current diagnostic standards. This also applies to serum marker screening (the so-called triple test) in the second trimester with the exception of rare late pregnancy confirmation.Therefore, professional organizations in many countries support a combined test according to the recommendations of the Fetal Medicine Foundation (FMF) UK and the FMF Germany 235. Using different algorithms for individual risk calculations, both approaches integrate standardized quality assurance requirements for NT measurement which is technically challenging and highly dependent on the experience of the operator. For risk calculations the use of NT measurements not meeting the recognized quality criteria is discouraged and sufficient qualification including annual renewal of certification is required.The rate of invasive procedures dropped by approximately 50 % after the introduction of the combined test during the last decade, while the detection rate increased to 90 %. This has been confirmed in single centers as well as by reports from countries with an established screening program, e. g. Denmark 6.On the downside, even 10 years after the broad introduction of the so-called first trimester test, significant effort is still required to secure standardization of NT measurement, which is error-prone and operator-dependent and requires dedicated training in addition to the regular curriculum. Moreover, continuous supervision by an expert panel with an annual audit for recertification seems mandatory but entails a substantial organizational expenditure.For decades some research groups have pursued the vision of a noninvasive method for detecting fetal chromosomal disorders in the maternal blood. For many years they focused on fetal cells (nucleated erythrocytes and trophoblast cells) in order to test for common aneuploidies in a simple maternal blood sample. An NIH-sponsored collaborative trial, however, provided ample evidence that this approach was unsuitable for routine testing 7. The demonstration of cell-free fetal DNA fragments in maternal plasma more than ten years ago and the later availability of high throughput sequencing at affordable costs finally led to a breakthrough in NIPT. Most published case series included pregnancies at increased risk for chromosome anomalies and tested for trisomies 21, 13, and 18. Cell-free fetal DNA is also successfully used for noninvasive Rhesus testing and sex determination in cases of sex-specific disease risks.The analysis is based on the quantification of chromosome-specific DNA fragments in maternal plasma 8. The percentage of cell-free fetal DNA originating almost exclusively from the cytotrophoblast is only about 10 % on average. Another diagnostic approach uses single nucleotide polymorphisms (SNPs) of the cfDNA. Published evidence confirms a sensitivity of NIPT in excess of 99 % and a false-positive rate of significantly less than 1 % for trisomies 21 and 18 and indicates a superior test performance for trisomy 21. The inclusion of other chromosome anomalies in the future is highly likely. NIPT is currently available worldwide despite ongoing patent litigation involving multiple companies 9.Independent experts and professional organizations currently consider NIPT not to be diagnostic due to false-positive and false-negative results but rather to be an advanced screening tool 8. There is also consensus regarding certain requirements which must be met for NIPT 1011.Comprehensive counseling regarding the different prenatal diagnostic options including all benefits and limitations of the individual approaches as legally required by the Law on Genetic Testing in Humans is obligatory. An ultrasound scan prior to testing should be inconspicuous without indication for chromosomal anomalies or other untreatable fetal diseases. A targeted malformation scan should precede NIPT considering the high costs and relatively long duration of the test. Therefore, NIPT should not be scheduled earlier than at 11 + 0 weeks of gestation in order to be able to exclude severe anomalies such as anencephaly as well as markers for trisomy 18 or 13 such as holoprosencephaly, hygroma colli, omphalocele, etc. Since an increased nuchal translucency may also indicate other structural chromosomal disorders, syndromes, and isolated malformations, the benefit of these markers and ultrasound at 11 – 14 weeks of gestation remains uncontested.Following NIPT a targeted malformation scan should be recommended at 20 to 22 weeks of gestation. It remains to be settled whether the sonographic examinations and consequently NIPT should be restricted to centers or specially trained operators or be integrated into basic screening.After a negative NIPT, a small residual risk for the trisomies included in the test as well as an unchanged risk for chromosome anomalies not included in the test will remain. General screening of low-risk pregnancies is currently not recommended due to a lack of data for this group as well as for multiples.Available performance data are primarily based on pregnancies with an increased risk for trisomies 21, 18, and 13 after an abnormal first trimester test or due to an advanced maternal age.In low-risk pregnancies and for rare trisomies, the probability of a false-positive result may be higher than for a true-positive test result 12. Morain et al. 1 noted that the prevalence of trisomy 21 in most series is very high (up to 1:8) producing impressively high positive predictive values (PPV) of 97.94 % and negative predictive values (NPV) of 99.99 %. For a prevalence of 1:200, the PPV would drop to 62.59 %. This supports the position to currently not use NIPT as a diagnostic test and to confirm all positive test results by conventional karyotyping prior to termination of pregnancy. This by no means lessens the significant benefit of NIPT as an advanced screening test.In many comments and reports the term “high risk pregnancies” is used but not defined in detail. In true high-risk cases with abnormal ultrasound findings or a risk of > 1:50 after a first trimester test, a comprehensive chromosome analysis requiring an invasive procedure is still recommended because of the high proportion of unbalanced chromosome counts not covered by NIPT 10. This is one of the reasons that some experts favor a regulation which restricts NIPT requests to specialized ultrasound centers.In summary, NIPT is an additional test which does not replace but complements invasive chromosome testing, the first trimester test and sonographic nuchal translucency measurements. In fact, the role of ultrasound for the exclusion of malformations as well as risk assessment prior to clinical and diagnostic decision-making is rather strengthened. Regulations and screening strategies have to be settled. Options currently being evaluated include stepwise screening following the first trimester test or contingent screening. The relevant professional organizations should establish an ongoing evaluation of these concepts. As a prenatal genetic test, NIPT is regulated by the Law on Genetic Testing in Humans and requires signed informed consent. International professional organizations currently recommend a first trimester test prior to NIPT as a basis for decision-making. Depending on the result and ultrasound findings, a choice between noninvasive and invasive testing may be made. Should the uptake of NIPT increase in the future, the number of invasive procedures including their sequelae such as procedure-related abortion and other complications will drop significantly.The first trimester test for risk assessment should currently be offered to all pregnant women. Doctors providing pre-test counseling should be aware that the benefits and limitations may be difficult to communicate. The introduction of NIPT has made counseling even more complex. From an ethical standpoint, it must be ensured that the requirements for an autonomous decision are met and sufficient time for consideration is provided in order to prevent automatisms in decision-making. Moreover, every pregnant woman should have access to formal genetic counseling. It has to be kept in mind that NIPT may be abused for sex selection. According to the Law on Genetic Testing in Humans, this is explicitly forbidden and all measures must be taken to prevent misuse.